Appearance of the acoustic and electromagnetic lateral wave in propagation phenomena - SNAKOWSKA, A. (Archives of Acoustics, 2005)
The paper presents the appearance of lateral waves of the acoustic and electromagnetic type in various physical phenomena, from the earthquakes up to ultra-high frequency radio-wave propagation in stratified medium. The lateral wave appears in the process of wave refraction to the medium characterized by higher wave speed, if the angle of incidence exceeds the critical value. The lateral wave arrives at the receiver first and in some cases is the only remaining wave at long distances, thus it plays an important role in early warning, wireless communication in lossy environments or ground penetrating radar applications, when geometric optic model leads to significant errors.